2023
DOI: 10.3390/brainsci13091310
|View full text |Cite
|
Sign up to set email alerts
|

Are Sex Differences in Collegiate and High School Sports-Related Concussion Reflected in the Guidelines? A Scoping Review

Patryk A. Musko,
Andreas K. Demetriades

Abstract: Background: Sport-related concussion (SRC) is a common sport injury. Females are participating in sports at increasing rates, and there is growing awareness that female athletes may be more vulnerable to SRC. Objectives: We aimed to identify sex differences in epidemiology, clinical manifestation and assessment of SRC and examine how these relate to the 6th International Conference on Concussion in Sport (ICCS). Methods: We conducted a scoping review of the Medline database and identified 58 studies examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Additionally, the discrepancies in guidelines could further contribute to existing lack of clarity in the management of SRCs in female athletes and put them at higher risk of developing poorer outcomes. Further discussion is required on this topic by soccer governing associations to determine whether a specific protocol needs to be developed for female athletes ( Musko and Demetriades, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the discrepancies in guidelines could further contribute to existing lack of clarity in the management of SRCs in female athletes and put them at higher risk of developing poorer outcomes. Further discussion is required on this topic by soccer governing associations to determine whether a specific protocol needs to be developed for female athletes ( Musko and Demetriades, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies done looking at trends in clinical practice with regards to standardisation of clinical practice with guidelines to increase the efficiency of managing patients and improving their outcomes ( Schoenbaum and Sundwall, 1995 ). However, there are also studies suggesting that some degree of variation and customisation from guidelines is beneficial when taking into the account the individuality of each patient and their clinical presentation ( Musko and Demetriades, 2023 ; Woolf et al, 1999 ; Van Haitsma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest a sexual dimorphism in TBI responses (see details in review by Gupte et al, 2019). Men are three-times more likely than women to die from TBI, and women often have worse symptom burdens and take longer time to recovery [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Multiple factors impact the outcome measurement of a TBI.…”
Section: Sex-biased Mirnas In Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…Some studies have reported no difference in miRNA expression profiles between males and females [ 158 ]. Nevertheless, it is encouraging that gender/sex has now been integrated as a biological variable in many recent TBI-related miRNA clinical studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 148 , 149 , 150 , 151 , 152 ].…”
Section: Sex-biased Mirnas In Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
See 1 more Smart Citation